2011
DOI: 10.1007/s11695-011-0487-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bypass Does Not Influence Olfactory Function in Obese Patients

Abstract: Morbidly obese individuals have altered sense of taste and smell. Gastric bypass (GBP) alters taste but olfactory function has not been evaluated. Changes in these senses may influence dietary preferences following GBP. Our aim was to evaluate the effect of abdominal operation, specifically GBP, and weight loss on olfactory function. Fifty-five persons undergoing GBP and cholecystectomy and 40 persons undergoing cholecystectomy (CC) alone were administered the Cross Cultural Smell Identification Test (CC-SIT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…In concordance with this potential explanation, recently in animal models, these findings were also replicated and found that smell capacity was diminished after hyperlipidemic diet [39]. This dysfunctional smell capacity in obese patients was even perpetuated after bariatric surgery and weight reduction [40]. Therefore, we may argue that in obesity, smell function might be a simple consequence of abnormal eating and extreme weight.…”
Section: Discussionsupporting
confidence: 75%
“…In concordance with this potential explanation, recently in animal models, these findings were also replicated and found that smell capacity was diminished after hyperlipidemic diet [39]. This dysfunctional smell capacity in obese patients was even perpetuated after bariatric surgery and weight reduction [40]. Therefore, we may argue that in obesity, smell function might be a simple consequence of abnormal eating and extreme weight.…”
Section: Discussionsupporting
confidence: 75%
“…Studies with humans and model organisms, especially obese-prone rats, even suggested the differences in olfactory abilities as a factor for the development of obesity [18,24]. Patients with metabolic disorders are known to have reduced olfactory abilities and studies indicated a clear decrease in olfaction with an increase in BMI [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al [18] studied the olfactory abilities of 55 morbidly obese patients who underwent gastric bypass surgery using Cross-Cultural Smell Identification Test and detected no change in olfaction in 12 months of follow-up period. On the contrary, Graham et al [30] in their study on 103 patients who underwent Roux-en-Y gastric bypass surgery reported change in the smell of 42 % of the subjects about 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Gustatory sensitivity, namely, taste acuity, is associated with oral stimulation, which determines food choice, amount consumed, and initiation and sensation of eating and thereby directly affects the nutritional status of a person. [3][4][5][6][7] Although taste is one of the important factors in a patient's quality of life, 8,9 compared to numerous studies on the olfactory sensitivity of obese patients, [10][11][12] there are only a number of studies in gustatory sensitivity of obese patients before or after surgical treatment. In addition, most of these studies focused on the change in sweet taste sensitivity of obese patients, probably due to association of leptin, a hormone regulating food intake, energy expenditure, and body weight with sweet taste threshold.…”
Section: Introductionmentioning
confidence: 99%